437 Impact of COVID-19 on West of Scotland Colorectal Cancer Services. (12th October 2021) - Welsh, S; Al-Ani, A
Abstract: Aim: The coronavirus disease 19 (COVID-19) pandemic has driven unprecedented restriction of the National Health Service to accommodate additional pressures. Our aim was to analyse the impact of COVID-19 on the largest colorectal cancer (CRC) services in NHS Greater Glasgow & Clyde. Method: Audit data collected from multidisciplinary team meetings for South Glasgow CRC service were accessed. We compared April-June 2020 ('Lockdown group') to corresponding months in 2019 ('Control group'). Statistical analysis by unpaired T-test, Pearson's χ2 test with post hoc analysis using adjusted Z scores and Bonferroni correction as appropriate. Results: There was a 39.5% reduction in CRC diagnoses during lockdown (n = 49) compared to control (n = 81). There was a 34.1% reduction in CRC operations during lockdown (n = 27) compared to control (n = 52). The proportion of patients managed operatively did not differ between groups (p = 0.140). There was no difference in the number of days from diagnosis to first treatment between Lockdown and Control groups (Mean(SD): 40.1±35.3 and 43.2±42.9, p = 0.257). Primary care physicians were the main referral source for both lockdown (52%) and control groups (46%). The cessation of bowel screening programme saw no referrals in lockdown whereas it accounted for 21% of referrals in control group, p < 0.001). Conclusions: We experienced dramatic reductions in CRC diagnoses during lockdown that was not only accounted for by the cessation of bowel screening. The diagnostic delay in the 39.5% 'missed' CRC patients may result in patient morbidity; a severe repercussion of COVID-19. The resurgence of COVID-19 cases poses a real threat to cancer services.